2011
DOI: 10.33225/pmc/11.02.36
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Teacher Burnout in Georgian Context

Abstract: Modern schools have multiple demands to teachers causing prolonged stress often resulting in professional burnout. Research on teacher burnout is conducted at various countries of the world. Taking into account the significance of such research, two pilot research studies were conducted in Georgia. The objectives of the studies were to test the hypothesis that the majority of Georgian teachers are experiencing high burnout and simultaneously to test the adopted translated instruments for measuring burnout and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Hunter [10] found that concerns about people management in organizations, lack of university autonomy, and the influence of higher education ministries can impact employees' behavior, as seen in employment challenges faced by administrative staff in Malaysia following COVID-19. Bitsadze and Japaridze [13] emphasize the significance of studying SHRM and organizational commitment (OC) in specific contexts, particularly in Georgia. They also highlight the need for future research on strategic decision-making, self-evaluation of research personnel, and commitment to continuous development in Georgian educational institutions to align with European higher education standards [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hunter [10] found that concerns about people management in organizations, lack of university autonomy, and the influence of higher education ministries can impact employees' behavior, as seen in employment challenges faced by administrative staff in Malaysia following COVID-19. Bitsadze and Japaridze [13] emphasize the significance of studying SHRM and organizational commitment (OC) in specific contexts, particularly in Georgia. They also highlight the need for future research on strategic decision-making, self-evaluation of research personnel, and commitment to continuous development in Georgian educational institutions to align with European higher education standards [14].…”
Section: Introductionmentioning
confidence: 99%